2013
DOI: 10.1111/risa.12101
|View full text |Cite
|
Sign up to set email alerts
|

The Use of PBPK Models to Inform Human Health Risk Assessment: Case Study on Perchlorate and Radioiodide Human Lifestage Models

Abstract: Physiologically-based pharmacokinetic (PBPK) models are often submitted to or selected by agencies, such as the U.S. Environmental Protection Agency (U.S. EPA) and Agency for Toxic Substances and Disease Registry, for consideration for application in human health risk assessment (HHRA). Recently, U.S. EPA evaluated the human PBPK models for perchlorate and radioiodide for their ability to estimate the relative sensitivity of perchlorate inhibition on thyroidal radioiodide uptake for various population groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For breast-fed infants, the thyroid iodine uptake inhibition almost doubled was predicted by the corrected models in comparison to those developed by Clewell and coworkers (e.g. The CONTAM Panel concluded that in view of the limited information available on the changes in thyroid hormone levels under conditions of mild to moderate iodine deficiency and on the thyroid hormone kinetic parameters for pregnant women, and the limitations of the PBK model predictability for iodine-deficient individuals identified by Clewell et al (2007) and McLanahan et al (2014), the results of the BBDR model at low iodine intake should be interpreted with caution. per day, thyroid iodine uptake inhibitions of 17 % and 8 % were predicted by the revised PBK model and the model from Clewell and coworkers, respectively.…”
Section: Physiologically-based Kinetic Modellingmentioning
confidence: 85%
See 3 more Smart Citations
“…For breast-fed infants, the thyroid iodine uptake inhibition almost doubled was predicted by the corrected models in comparison to those developed by Clewell and coworkers (e.g. The CONTAM Panel concluded that in view of the limited information available on the changes in thyroid hormone levels under conditions of mild to moderate iodine deficiency and on the thyroid hormone kinetic parameters for pregnant women, and the limitations of the PBK model predictability for iodine-deficient individuals identified by Clewell et al (2007) and McLanahan et al (2014), the results of the BBDR model at low iodine intake should be interpreted with caution. per day, thyroid iodine uptake inhibitions of 17 % and 8 % were predicted by the revised PBK model and the model from Clewell and coworkers, respectively.…”
Section: Physiologically-based Kinetic Modellingmentioning
confidence: 85%
“…The corrected models were applied to estimate the thyroid iodine uptake inhibition under a steady state perchlorate concentration. The predictions of the corrected models developed by McLanahan et al (2014) were compared to those of the models developed by Clewell and coworkers, showing a good correlation for all life stages, with the exception of the breast-fed infants and lactating women. For breast-fed infants, the thyroid iodine uptake inhibition almost doubled was predicted by the corrected models in comparison to those developed by Clewell and coworkers (e.g.…”
Section: Physiologically-based Kinetic Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…We should keep in mind that it is not necessarily the concentration (as peak concentration or area under the curve) that matters, but that some lipophilic (see example in Fig. 4) to predict the internal dose that will be distributed to target organs, and they are increasingly being used in risk assessment across industries (McLanahan et al, 2014). They can be used for in vitro to in vivo, route to route, and animal to human extrapolations (Basketter et al, 2012;Espié et al, 2009;Rietjens et al, 2011).…”
Section: In Vitro Pharmacokineticsmentioning
confidence: 99%